PENAMBAHAN BEBERAPA KONSENTRASI XANTHAN GUM TERHADAP MUTU SAOS TOMAT (Solanum lycopersicum Lin.,) - Hamzah, Faizah; Harun, Noviar; ', Wandestri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to obtain the best concentration of xanthan gum to quality of tomato sauce. This research used a Completely Randomized Design (CRD) with 4 treatments and 4 replications this obtaining 16 experimental units. The data obtained were stasitiscally analyzed of variance (Anova) if the F countis greater than or aqual to F table then continued with DNMRT tes at 5% level. Results of variance showed different that xanthan gum concentration significantly affect the degree of acidity (pH), total dissolved solids, viscosity, sweetness is descriptive test, assement of the overall hedonic test and had no significant affect on the descriptive colour and flavor. The best formulation of tomato sauce is treatment T3 (xanthan gum concentration 0,6%) with  shows a pH 4,15,  the total dissolved solids 26,13 obrix, and viscosity 14593 cP.   Keywords: Tomato, Tomato sauce, Xanthan gum